Developments and applications of nanomaterial-based carbon paste electrodes - Tajik, Somayeh; Beitollahi, Hadi; Nejad, Fariba Garkani; Safaei, Mohadeseh; Zhang, Kaiqiang; Van Le, Quyet; Varma, Rajender S; Jang, Ho Won; Shokouhimehr, Mohammadreza (RSC advances, 2020)
This review summarizes the progress that has been made in the past ten years in the field of electrochemical sensing using nanomaterial-based carbon paste electrodes. Following an introduction into the field, a first large section covers sensors for biological species and pharmaceutical compounds (with subsections on sensors for antioxidants, catecholamines and amino acids). The next section covers sensors for environmental pollutants (with subsections on sensors for pesticides and heavy metal ions). Several tables are presented that give an overview on the wealth of methods (differential pulse voltammetry, square wave voltammetry, amperometry, etc.) and different nanomaterials available. A concluding section summarizes the status, addresses future challenges, and gives an outlook on potential trends.